Método de controle de trajetória de atuadores ipmc baseados em nafion® utilizando técnica de visão de máquina em ambiente com umidade relativa controlada - Zuquello, Ariel Gustavo (2021)
Ionomeric polymer-metal composites (IPMC) consist of an electroactive polymeric matrix coated on both sides with a noble metal. When applying an electrical potential difference, the polymeric membrane changes its thickness, causing a deformation. In addition, this type of device has features such as low weight, flexibility, and biocompatibility. Therefore, as actuators, IPMCs are a good choice for applications such as robotics and biomedicine. However, they have some disadvantages, such as reverse relaxation (tendency to shift in the opposite direction to that defined after some time of operation) and non-linear behavior arising from the hydration level of the polymeric membrane. For these reasons, controlling and describing the mechanical responses of these devices has been a challenge. Therefore, the overall objective of this study was to develop an effective system and instrumentation to control and characterize IPMC actuators under varying moisture and counter-ion conditions. A closed-loop PI controller (Proportional and Integral) aggregate with a machine vision algorithm was used. In this approach, a webcam is responsible for tracking the actuator's movement. However, it was necessary to perform some morphological and electrical characterizations beforehand to understand the properties and thus determine the best control condition for an IPMC actuator. Among them, water adsorption capacity, scanning electron microscopy, four probe method, impedance spectroscopy, and chronoamperometry. The entire system operates simultaneously and is controlled in real-time by LabView. The results prove that the system developed in this study effectively circumventing the reverse relaxation phenomenon and correlating control parameters with material properties.